A simple and general approach for the synthesis of biodegradable triblock copolymers by organocatalytic ROP from poly(lactide) macroinitiators. (15th March 2020) - Toshikj, Nikola; Robin, Jean-Jacques; Blanquer, Sebastien
Graphical abstract: Highlights: Synthesis of biodegradable PTMC- b -PDLLA- b -PTMC and PCL- b -PDLLA- b -PCL triblock copolymers by ring opening polymerization. General approach for biodegradable triblock copolymer synthesis with PDLLA first route with no side reactions. Study of the catalytic influence on the block copolymerization when PDLLA is employed as macroinitiator. Effective triblock copolymerization is obtained using cationic activated monomer mechanism. One pot sequential copolymerization is achieved via traceless switch organocatalysis approach. Abstract: To overcome the present limitations in the synthesis of biodegradable triblock copolymers with PLA as central building block, three different reactional mechanisms (coordination-insertion, anionic and cationic) have been involved, while employing the transition from organometallic to organic catalysis. Even though activated chain-end mechanism with stannous octanoate is well known for the successful ROP catalytic reactivity, the synthesis of PLA based triblock copolymers according to this route revealed not negligible transesterification reactions. In the same way, the activated chain-end mechanism through nucleophilic activation (TBD) presented either no reactivity or weak control over the anionic polymerization process. Herein, we therefore propose an activated monomer mechanism as general and simple route for obtaining controlled PTMC- b -PDLLA- b -PTMC and PCL- b -PDLLA- b -PCL triblock copolymers by using cationic organocatalysis (MSA). 1 H, 13 C NMR and DOSY-NMR spectra confirmed the well-controlled polymer architecture of the B-A-B triblock copolymer.